Hypoxic cardiopulmonary arrest with full recovery after induced hypothermic therapy. Issue 2 (18th December 2013) - Matsuo, Tomoji; Yanagawa, Youichi; Takeuchi, Yuji; Inoue, Teruhiro; Oomori, Kazuhiko; Osaka, Hiromichi; Hayashi, Nobuhiro; Oode, Yasumasa; Shimizu, Takashi; Sato, Nobuyuki; Okamoto, Ken
<x xml:space="preserve">Abstract</x> Case The patient's chart was reviewed, summarized, and presented. Outcome A 41‐year‐old male collapsed after complaining of dyspnea just before the end of a hemodialysis session. He was just being introduced to hemodialysis. The patient's percutaneous oxygen saturation dropped to 50% even under inhalation of 10 L/minute of oxygen and he developed pulseless electrical activity. After tracheal intubation, a return of spontaneous circulation was noted. His truncal CT disclosed a bilateral diffuse ground glass appearance and pleural effusion were noted. Induced mild hypothermic therapy and mechanical ventilation resulted in the improvement of his respiratory function and consciousness. A coronary angiogram and left ventriculography showed no significant lesion, and his pulmonary edema was considered to have been induced by over‐hydration due to renal failure, diastolic heart failure or dialysis disequilibrium syndrome. He was discharged without any neurological deficit. Conclusion Tracheal intubation with ventilation for hypoxic cardiopulmonary arrest and induced hypothermic therapy after obtaining spontaneous circulation may be factors of favorable outcome of this case.